Strategi Fundraising Zakat, Infaq dan Sedekah Melalui Sistem Berbayar Non-Tunai Quick Response Code Indonesian Standard (Qris) di Baznas Kota Palopo - Nurul; Nispa; Andika (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study is to see how far the implementation of the strategy of fundraising zakat funds using the QRIS no-cash paid system and how the flow of zakat payments through QRIS in BAZNAS Palopo City district. This research is a field research with a qualitative descriptive approach, and data collection is obtained from interviews and field observations. The results of the study show that the implementation of the fundraising and zakat strategy using QRIS at BAZNAS Palopo City goes through several stages, namely determining Muzakki's segments and targets, preparing human resources, building a communication system and compiling a service system. Not only that, BAZNAS Palopo City also runs a marketing communication strategy. That is by making interesting programs, creating feelings of empathy, collaborating with other companies, and providing the best service. To process zakat payments with QRIS, muzakki only need to scan the QR code for zakat payments at BAZNAS Palopo City, then follow the next payment steps. In a matter of minutes and without going to the BAZNAS Palopo City office, muzakki can pay their zakat whenever and wherever they are.